Phytochemical Analysis, Cytotoxicity, Antibacterial and Antioxidant Activities of Extracts of Leaf of Ageratina adenophora (Spreng.) - Thapa, Arjun; Pokharel, Aaradhana; Karki, Homa; Yadav, Rakesh Kumar; Paudel, Namuna; Bharati, Samjhana; Shrestha, Timila; Maharjan, Binita; Karanjit, Sangita; Shrestha, Ram Lal (Amrit Research Journal, 2022)
The powdered leaf of Ageratina adenophora was subjected to extraction using a cold percolation method with methanol. After suspending the crude methanol extract in 1% HCl and neutralizing with NH4OH, the obtained solution was extracted with hexane, chloroform, and ethyl acetate solvent, respectively. Qualitative phytochemical analysis of methanol, hexane, chloroform, and ethyl acetate extracts of A. adenophora plant showed the presence of alkaloids, flavonoids, phenols, steroids, quinones, saponins, tannins, cardiac glycosides, carbohydrate, terpenoids, proteins, and amino acids. GC-MS analysis of chloroform extract showed 10 different major compounds in which α-Muurolol (24.33%) was found most abundant. The IC50 value of chloroform extract was found to be 1460 µg/mL from DPPH scavenging antioxidant assay, and the LC50 value was found to be 174.78 µg/mL from the brine shrimp lethality assay. Antibacterial activity was shown the highest against Escherichia coli and Proteus vulgaris with ZOI of 12 mm on each in chloroform extract. It was determined that 89.75 mg of gallic acid equivalent/g of dry extract accounted up the total phenolic content and 49.25 mg of quercetin equivalent/g of dry extract was observed to be the total flavonoid content in the chloroform extract.